Isolation of yeast from soil and different food samples and its characterization based on fermentation - Thapa, Sandeep; Shrestha, Rajani; Tirewal, Anjali; Sharma, Arjun; K.C., Yuvraj (Nepal Journal of Biotechnology, 2015)
Yeasts are eukaryotic microorganisms which can also be used for bioethanol production. In this modern era of increasing demand for energy and fuel, the microbial biosynthesis of ethanol has gained importance. In this study, the potential yeasts for ethanol production from pentose and hexose sugars were identified. Yeasts were isolated from soil and different food samples. They were identified and characterized based on cell morphology (e.g., mode of cell division and spore shape) and physiology (e.g., sugar fermentation tests). Furthermore, quantification of ethanol and cell concentration was performed throughout the fermentation. Spot plate count method was followed to determine the viable yeast count whereas Potassium dichromate oxidation method was used for determining the ethanol concentration. Six different species of yeasts were cultured in three sets of broth for 24, 48, 72, and 96 hours for bioethanol production. The yeasts isolated from black and green grapes relatively synthesized higher concentration of ethanol. Nepal Journal of Biotechnology. Dec. 2015 Vol. 3, No. 1: 29-34